The Relationship between Knowledge and Attitude of the Elderly in Handwashing as an Effort to Prevent Covid-19 - Gultom, Desi Meliana; Hasibuan, Evi Erianty; Sari, Elpiana; Batubara, Fitria Lely Effina (International Journal of Public Health Excellence (IJPHE), 2022)
Data updated by the Indonesian Ministry of Health on February 17, 2020, WHO has designated Covid-2019 as a Public Health Emergency of International Concern (PHEIC) due to a significant increase in cases and confirmed cases in several other countries. The New England Journal of Medicine (NEJM) on January 29, 2020 summarized the first 425 cases recorded in Wuhan. The data show that the mean age of the patients was 59 years, with a range of 15 to 89 years. This study aims to determine the relationship between knowledge and the attitude of the elderly in washing their hands as an effort to prevent Covid-19. This type of research is analytic observational with cross sectional design. The research sample was 21 elderly people. The data analysis used was univariate analysis, bivariate analysis and multivariate analysis with chi square test with p value < 0.05. There is a relationship between knowledge and attitude with elderly hand washing as an effort to prevent COVID-19 in 2020 with a p value < 0.05. It is hoped that all parties can cooperate in disseminating health protocols, especially hand washing and the provision of hand washing facilities as a form of COVID-19 prevention efforts.